Consumer protection: the role of the State and society - Schwalb, María Matilde (1993)
​This article emphasises the importance of consumer protection and calls on all the groups and sectors involved to adopt a positive, active attitude in defence of consumer rigths. Although the government has recently implemented important reforms in this area, existing legislation still needs to be perfected and swift mechanisms introduced that enable the consumer to effectively and efficiently defend his interests. On this point the authoress suggests a number of possible courses of action for suppliers, non-profitable private organizations –among which the important work being done by universities plays a leading role- and for the consumers themselves.